LRRTM2 controls presynapse nano-organization and AMPA receptor sub-positioning through Neurexin-binding interface - Konstantina Liouta; Malgorzata Lubas; Vasika Venugopal; Julia Chabbert; Caroline Jeannière; Candice Diaz; Matthieu Munier; Béatrice Tessier; Stéphane Claverol; Alexandre Favereaux; Matthieu Sainlos; Joris de Wit; et al. (Nature Communications, 2024)
Abstract Synapses are organized into nanocolumns that control synaptic transmission efficacy through precise alignment of postsynaptic neurotransmitter receptors and presynaptic release sites. Recent evidence show that Leucine-Rich Repeat Transmembrane protein LRRTM2, highly enriched and confined at synapses, interacts with Neurexins through its C-terminal cap, but the role of this binding interface has not been explored in synapse formation and function. Here, we develop a conditional knock-out mouse model (cKO) to address the molecular mechanisms of LRRTM2 regulation, and its role in synapse organization and function. We show that LRRTM2 cKO specifically impairs excitatory synapse formation and function in mice. Surface expression, synaptic clustering, and membrane dynamics of LRRTM2 are tightly controlled by selective motifs in the C-terminal domain. Conversely, the N-terminal domain controls presynapse nano-organization and postsynapse AMPAR sub-positioning and stabilization through the recently identified Neurexin-binding interface. Thus, we identify LRRTM2 as a central organizer of pre- and post- excitatory synapse nanostructure through interaction with presynaptic Neurexins.